2004
DOI: 10.1055/s-2004-831850
|View full text |Cite
|
Sign up to set email alerts
|

Expressionsmuster und prognostische Bedeutung von CD24, p53 und p21 in Lymphomen

Abstract: The TMA-technology allows also in lymphoma research the simultanous, cost-effective and standardized analysis of large patient cohorts. Deltap53 revealed as an independent negative prognostic factor in diffuse large B-cell lymphomas. It can easily be determined in daily routine practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…Despite CD24 being used as a differentiation marker of lymphocytes in the hematology field, only a few studies have reported on CD24 in mature B-cell lymphoma related to its expression and clinical impact. Went et al reported that CD24 was expressed in 0-20% of mature B-cell lymphoma, depending on the subtype of B-cell lymphoma, and expressed in 9% of DLBCL cases [32]. The frequency of CD24 expression in DLBCL was comparable to our IHC results.…”
Section: Discussionsupporting
confidence: 88%
“…Despite CD24 being used as a differentiation marker of lymphocytes in the hematology field, only a few studies have reported on CD24 in mature B-cell lymphoma related to its expression and clinical impact. Went et al reported that CD24 was expressed in 0-20% of mature B-cell lymphoma, depending on the subtype of B-cell lymphoma, and expressed in 9% of DLBCL cases [32]. The frequency of CD24 expression in DLBCL was comparable to our IHC results.…”
Section: Discussionsupporting
confidence: 88%
“…Some studies showed that the p53 + /p21 − (Δ p53 ) immunophenotype, used as a surrogate for p53 mutations, is associated with treatment failure and poor survival in DLBCL as well, particularly in GC DLBCL (Moller et al 1999; Pagano et al 2001; Visco et al 2006). We recently performed a TMA-based study on 297 DLBCL considering the prognostic significance Δ p53 (Went et al 2004), which was found in 21% of cases. In a multivariate model, high IPI and Δ p53 were independent prognostic markers of poor survival.…”
Section: Prognostic Significance Of Immunophenotypic Cell Cycle-and Amentioning
confidence: 99%
“…Taking into consideration these statistic operators, we critically re-evaluated our own TMA series of 301 primary DLBCL (Tzankov et al 2003a; Went et al 2004; Zinzani et al 2005; Tzankov et al 2005a; Tzankov et al 2006) to determine the optimal cut-off values for differentiation-associated antigen expression (Table 2). We linked the results to the clinical end-point “disease-related mortality” and critically compared the outcomes obtained considering the cut-off levels form the ROC curves and Y with those suggested in the literature.…”
Section: Implementation Of Receiver Operating Characteristic (Roc) Cumentioning
confidence: 99%
See 1 more Smart Citation